BENTUK KETERBUKAAN RAHASIA MEDIS DALAM SITUASI PANDEMI VIRUS COVID 19 DI INDONESIA - Afdhal Afdhal; Irvansyah Irvansyah (JURNAL AKTA YUDISIA, 2021)
The right to confidentiality or privacy is something unique between a patient's relationship with a doctor because it is based on trust. This patient-doctor relationship is unique because the patient believes in the doctor's ability and the patient believes the doctor will keep the patient's secret. The influence of the covid 19 outbreak has made people nervous and afraid because the virus is very easy to spread and spreads globally. The community asks to open data related to the secrets of Covid 19 patients, both in the form of names, addresses, symptoms, diagnosis, and interactions that have been made. Patient data which is classified as a basic right to privacy is an important component in breaking the chain of the spread of Covid 19 because the government has implemented large-scale social restrictions in certain areas to maintain social interactions so that the community can avoid exposure to this virus. This needs to be studied in depth regarding the Forms of Disclosure of Medical Secrets in the PANDEMIC Covid 19 Situation in Indonesia.This type of research is normative juridical research or what is known as doctrinal research. Normative juridical research is research that looks at problems through the aims and objectives to be achieved using surgical tools in the form of statutory regulations and regulations in a formal hierarchy of regulations as well as theoretical studies of updated and modern literature.Covid 19 Patient Information is data stored in medical records that can be provided based on patient consent or the law. But in Article 57 paragraph (2) of Health Law, the right to confidentiality is excluded, one of which is for the benefit of society. The doctor's obligation to keep information related to the patient's medical condition is an obligation as described in the Republic of Indonesia Minister of Health Regulation Number 269 / MENKES / PER / III / 2008 concerning Medical Records but in the event of an outbreak or pandemic covid 19, the disclosure of secrets is carried out with the covid procedure, namely by evaluating the interaction of patients who have been in SWAB Positive and carry out self-isolation for COVID 19 patients without symptoms and medical isolation for patients with symptoms. Keyword: Information, Covid 19, Hukum, Privacy